Analisis Penggunaan Media Pembelajaran Papan Pecahan Kelas Tinggi di SD Negeri Periuk Jaya Permai Tangerang - Ismawanti, Agnes; Unaenah, Een; Putri, Disa Cahaya; Azzahra, Fernita Dwi (Lembaga Yasin AlSys, 2022)
Learning is a process of interaction between students or students with educators or teachers and learning resources in a learning environment that includes teachers and students exchanging information. In learning activities, of course there are other components to support these learning activities, namely learning media. In learning Mathematics, planting and understanding the concept of a material must attract students' interest and motivate students to understand more about the material and there are no misconceptions. This study aims to determine the use of high grade fractional board media at Periuk Jaya Permai Elementary School. The type of this research is observation, interview guide and researcher as instrument and key. The source of the data for this research is the results of interviews with teachers at the SDN. The resource person explained that students would be more enthusiastic and motivated if the teacher brought the fraction board media because it was more fun and less rigid in learning activities in class. For this reason, the teacher uses the fraction board learning media to attract students' interest. The conclusion obtained from this research is that by bringing the fraction board media the teacher feels that the media facilitates the learning process carried out. This will affect the implementation and success in learning the appropriate, correct, and correct fractions of mathematics material, and students do not experience misconceptions.